Work-family conflict among Hindu fathers in South Africa - Vanmali Kavesh (Organisational Psychology, 2018)
This research examined work-family conflict among Hindu fathers in South Africa. Various authors have indicated that work-family conflict should be investigated in specific cultural contexts because the demands of work and family differ across various cultures. This research examined the relationships between work role overload, supervisor support, coworker support and work-family conflict. Additionally, this research also examined the moderating role of traditional Hindu cultural values (gender role ideology and family hierarchy orientation) in the relationships between work role overload, supervisor support, and work-family conflict. Secondary data from an earlier study that explored work-family conflict among Hindu parents in South Africa was used. The final sample consisted of 183 Hindu fathers involved in full-time work in South Africa. Exploratory factor analysis confirmed the bi-directionality of the work-family conflict construct. Hierarchical regression analyses showed that work role overload and co-worker support were significant predictors of work-to-family conflict (W2FC), whilst work role overload was a significant predictor of family-to-work conflict (F2WC). Results of the moderated regression analyses showed that gender role ideology did not moderate the relationships between work role overload, W2FC and F2WC. Family hierarchy orientation did not moderate the relationships between supervisor support, W2FC and F2WC. The findings of this research have practical implications for management and offer suggestions for future research.